The Metaphoric Conceptualization of the Covid-19 Pandemic in the Online Press Releases of Lapor Covid-19 and Kominfo - Maria Magdalena Sinta Wardani (Journal of Language and Literature, 2021)
This article seeks to describe the metaphoric conceptualization of the COVID-19 pandemic in the online press releases of Lapor COVID-19 and the Ministry of Communication and Information Technology (Kominfo). More specifically, it seeks to 1) describe the metaphorical linguistic forms contained in the online press releases of Lapor COVID-19 and Kominfo, 2) identify the conceptual metaphors contained in the online press releases of Lapor COVID-19 and Kominfo, 3) describe the function of the metaphors contained in the online press releases of Lapor COVID-19 and Kominfo. Data were collected between March 1 and October 31, 2020. Analysis was conducted using the method developed by Steen (2009). Nine metaphors were identified as being used within the context of the COVID-19 pandemic: 1) berguguran ('fall in battle'), 2) berdamai ('make peace'), 3) garis depan ('frontlines'), 4) melawan ('oppose'), 5) menang ('win'), 6) benteng ('fortress, bastion'), 7) menghantui ('spook'), 8) membesar ('grow in size'), and 9) menelan ('swallow'). Three conceptual metaphorizations of the pandemic were utilized by Lapor COVID-19, namely 1) PANDEMIC IS WAR, 2) PANDEMIC IS GHOST/SPECTER, and 3) PANDEMIC IS MONSTER. Meanwhile, one conceptual metaphorization was identified in Kominfo's press releases: PANDEMIC IS WAR. These conceptual metaphors' selection was informed by the genre of the discourses as well as specific characteristics of the institutional. Metaphors, as rhetoric devices in persuasive discourses, function to 1) increase the attractiveness of the message and stimulate readers' imagination, 2) reduce the complexity of the message, and 3) to concretize the discourse.